2018
DOI: 10.1590/0074-02760170505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetation on cutaneous leishmaniasis in Paraná, Brazil

Abstract: BACKGROUND Cutaneous leishmaniasis (CL) is endemic in the state of Paraná, Brazil.OBJECTIVE This study aimed at analysing the influence of the remaining native vegetation on the prevalence of CL in Paraná.METHODS Global testing was used for spatial autocorrelation along with simultaneous autoregressive model (SAR). The regression was based on the CL coefficient (cases/100,000 inhabitants) as a function of the percentage of natural vegetation cover, altitude, total number of cases, and spatial density (SD) per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…The migration in areas with significant disease incidence, the urban/peri-urban expansion process, land settlements, hunting activities, and military training are some of the conditions that may adversely affect the occurrence of CL human cases (Melo et al, 2018). We found that the cutaneous form of leishmaniasis prevailed in the last years in Caxias, representing almost the total number of those infected.…”
Section: Discussionmentioning
confidence: 76%
“…The migration in areas with significant disease incidence, the urban/peri-urban expansion process, land settlements, hunting activities, and military training are some of the conditions that may adversely affect the occurrence of CL human cases (Melo et al, 2018). We found that the cutaneous form of leishmaniasis prevailed in the last years in Caxias, representing almost the total number of those infected.…”
Section: Discussionmentioning
confidence: 76%
“…In addition to the females consuming blood, both male and female sand flies regularly ingest plant-derived sugar meals as a source of energy. Because of the dependence of sand flies on plant meals, the structure of plant communities can affect the spatial and temporal distribution of sand fly populations (4). Moreover, certain plants upon which sand flies feed can shorten their life or reduce their capacity for transmitting leishmaniasis (5,6).…”
mentioning
confidence: 99%
“…Only two studies about leprosy were included, both conducted in Brazil regarding its epidemiology in Paraná State [58] and Foz do Iguaçú [30], despite leprosy being present in the three countries and a wellknown prevalent disease in Misiones, Paraná and Foz do Iguaçú [10,16,-58]. Overall, the five epidemiological studies included were related with past diseases outbreaks, namely two about leishmaniasis in Paraná [29] and Puerto Iguazú [55], one about dengue in Paraná [53] and the two about leprosy in Paraná [58] and Foz do Iguaçú [30].…”
Section: Resultsmentioning
confidence: 99%